Numerical simulation and first-order hazard analysis of large co-seismic tsunamis generated in the Puerto Rico trench: near-field impact on the North shore of Puerto Rico and far-field impact on the US East Coast - S. T. Grilli; S. Dubosq; N. Pophet; Y. Pérignon; J. T. Kirby; F. Shi (Natural Hazards and Earth System Sciences, 2010)
We perform numerical simulations of the coastal impact of large co-seismic tsunamis, initiated in the Puerto Rican trench, both in far-field areas along the upper US East coast (and other Caribbean islands), and in more detail in the near-field, along the Puerto Rico North Shore (PRNS). We first model a magnitude 9.1 extreme co-seismic source and then a smaller 8.7 magnitude source, which approximately correspond to 600 and 200 year return periods, respectively. In both cases, tsunami generation and propagation (both near- and far-field) are first performed in a coarse 2′ basin scale grid, with ETOPO2 bathymetry, using a fully nonlinear and dispersive long wave tsunami model (FUNWAVE). Coastal runup and inundation are then simulated for two selected areas, using finer coastal nested grids. Thus, a 15″ (450 m) grid is used to calculate detailed far-field impact along the US East Coast, from New Jersey to Maine, and a 3″ (90 m) grid (for the finest resolution), encompassing the entire PRNS, is used to compute detailed near-field impact along the PRNS (runup and inundation). To perform coastal simulations in nested grids, accurate bathymetry/topography databases are constructed by combining ETOPO2 2′ data (in deep water) and USGS' or NOAA's 15″ or 3″ (in shallow water) data. In the far-field, runup caused by the extreme 9.1 source would be severe (over 10 m) for some nearby Caribbean islands, but would only reach up to 3 m along the selected section of the East coast. A sensitivity analysis to the bathymetric resolution (for a constant 3″ model grid) of runup along the PRNS, confirms the convergence of runup results for a topographic resolution 24″ or better, and thus stresses the importance of using sufficiently resolved bathymetric data, in order to accurately predict extreme runup values, particularly when bathymetric focusing is significant. Runup (10–22 m) and inundation are found to be very large at most locations for the extreme 9.1 source. Both simulated spatial inundation snapshots and time series indicate, the inundation would be particularly severe near and around the low-lying city of San Juan. For the 8.7 source, runup along the PRNS would be much less severe (3–6 m), but still significant, while inundation would only be significant near and around San Juan. This first-order tsunami hazard analysis stresses the importance of conducting more detailed and comprehensive studies, particularly of tsunami hazard along the PRNS, for a more complete and realistic selection of sources; such work is ongoing as part of a US funded (NTHMP) tsunami inundation mapping effort in Puerto Rico.